From Frozen to Latent Conflicts. Is a New EU Paradigm for Bosnia and Herzegovina Urgent? - Kučukalić, Esma (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2022)
Three decades have passed since the beginning of the war, which ravaged Bosnia and Herzegovina (BiH), and the state finds itself once again in the quagmire of partitioning. In terms of high diplomacy, it is described as the worst crisis since the signing of the Dayton Peace Agreement (1995), which still needs to be consolidated and fully legitimised. The international document that stopped the bloodshed and, at the same time, plunged the state into a tortuous citizenship abyss made of political contradictions, together with an institutional framework instrumentalised as a fertile ground for stabilitocracy and geostrategic influence games. The war in Ukraine has revived the international community’s interest in BiH, forcing it to take firmer stances. This article aims to analyse the recent events in BiH and the European Union (EU)’s strategy in light of its complex relationship based on coherence and inconsistency and the idea of security. The research questions whether the EU will take advantage of the lessons learned in the bloody nineties to resolve frozen conflicts. Answers are provided through an argumentative research design comprising a qualitative analysis of the institutional structure of BiH and the review of the interrelationships between the state and the triggers of local, regional and international instability with a special focus on the EU. The Ukraine scenario shows how quickly frozen conflicts start burning.

Trzy dekady minęły od początku wojny, która spustoszyła Bośnię i Hercegowinę (BiH), a państwo ponownie znalazło się w grzęzawisku podziałów. W wysokiej dyplomacji określa się ją mianem najgorszego kryzysu od czasu podpisania poro zumienia pokojowego w Dayton (1995 r.), które nadal wymaga konsolidacji i pełnej legitymizacji. Ten międzynarodowy dokument zatrzymał rozlew krwi, a jednocześnie pogrążył państwo w krętej otchłani obywatelstwa złożonej z politycznych sprzeczności i ram instytucjonalnych zinstrumentalizowanych jako żyzny grunt dla stabilokracji i geostrategicznych gier wpływów. Wojna na Ukrainie ożywiła zainteresowanie społeczności międzynarodowej BiH, zmuszając ją do zajęcia bardziej zdecydowanego stanowiska. Niniejszy artykuł ma na celu analizę ostatnich wydarzeń w Bośni i Hercegowinie oraz strategii Unii Europejskiej (UE) w świetle jej złożonych relacji opartych na spójności i niespójności oraz idei bezpieczeństwa. Badania dotyczą tego, czy UE wykorzysta doświadczenia zdobyte w krwawych latach dziewięćdziesiątych do rozwiązania zamrożonych konfliktów. Odpowiedzi udziela się dzięki realizacji argumentacyjnego projektu badawczego obejmującego jakościową analizę struktury instytucjonalnej Bośni i Hercegowiny oraz przegląd wzajemnych powiązań między państwem a czynnikami wywołującymi niestabilność lokalną, regionalną i międzynarodową, ze szczególnym uwzględnieniem UE. Scenariusz ukraiński pokazuje, jak szybko zaczynają płonąć zamrożone konflikty.
Od zamrożonych do ukrytych konfliktów. Czy potrzeba nowego paradygmatu działań Unii Europejskiej wobec Bośni i Hercegowiny jest pilna?
Keywords: Bosnia and Herzegovina; Dayton; European Union; Counter-Europeanisation; stabilitocracy; Bośnia i Hercegowina; Dayton; Unia Europejska; kontreuropeizacja; stabilokracja